Study of Physico-Chemical Parameter of Deepang lake in Pokhara Valley, Nepal - Bastola, Shubhas C. (Janapriya Journal of Interdisciplinary Studies, 2017)
The present study on Physico-chemical Parameter of Deepang lake in Pokhara valley, Nepal was performed for six months from August 2009 to January 2010. The study included various physico-chemistry parameter like transparency, temperature, PH, free carbondioxide, dissolve oxygen and total alkalinity. The maximum transparency 2.5 m was recorded in January and minimum 1.4 m in August. In other months the transparency were slightly changeable. The maximum temperature 25.6°C was recorded in August and minimum 17.7°C in January. The temperature gradually decreased. The PH values were found mostly alkaline and were generally between 6.7 and 7.5 during the investigation period. The highest PH 7.5 was recorded in January and lowest 6.7 in August. Dissolved oxygen value gradually increased from 6.4 mg/l in August to 8.7 mg/l in January. The concentration of free CO2 ranged between 1.8 mg/l and 5.6 mg/l during the investigation period. The maximum value was 5.6 mg/l in August and 1.8 mg/l in January. The maximum alkaline value 114 mg/l was recorded in January and minimum value 105 mg/l in August. All these Physico-chemical parameter meet WHO Standard of Water Quality.   Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 90-95